AB0205 TREATMENT OF INFLAMMATORY MYOSITIS IN CLINICAL PRACTICE: ANALYSIS OF THE REGISTRY OF INFLAMMATORY MYOSITIS FROM THE MADRID COMMUNITY (REMICAM). (June 2019) - Joven-Ibáñez, Beatriz; Nuño, Laura; López-Longo, Francisco J.; Martinez-Barrio, Julia; Larena, Carmen; Maldonado, Valentina; Barbadillo, Carmen; Peña, Paloma García de la; Llorente, Irene; Muriel, Eva Tomero; Gómez, Ana Pérez; Moruno, Henry; et al.
Abstract : Background: Although glucocorticoids (GC) remain the cornerstone in the treatment of inflammatory myositis (IM), the management of these processes is not yet standardized. Experts recommend early use of immunosuppressants (IS), in order to prevent GC side effects. It is not known what is the actual management in clinical practice. Objectives: To describe the management of IM in REMICAM registry, and to identify differences according to disease subtype (polymyositis (PM), or dermatomyositis (DM)), and to the year of diagnosis (before or after 2000). Methods: All patients from REMICAM were included (1). A descriptive analysis of the different therapies (GC, IS, biologics, IV immunoglobulins (IVIG), and hydroxychloroquine HCL) was performed, attending to possible differences between IM subtype and the year of diagnosis. T student and Chi square tests were used for quantitative and qualitative variables, respectively. Results: From 479 patients (74% females, 52% PM, 44±22 y at diagnosis, 10±8 y follow up), 473 (99%) received oral GC, 50/344 (15%) pulses GC, 78 (16%) HCL, 355 (74%) IS (methotrexate MTX 228, leflunomide 10, azathioprine AZA190, cyclophosphamide 44, mycophenolate MP 38, cyclosporine 32), 55 (12%) biologics (rituximab 45, abatacept 2, aTNF 16) and 79 (17%) IVIG. Differences according to IM subtype (1), and to the year of diagnosis (2), are shown in Tables. Conclusion: The therapeutic management of IM has changed over the last few years, with a clear increase and earlier use of IS in patients diagnosed after 2000. In spite of a more aggressive approach in recent years, severe infections are less frequent, perhaps as a consequence of lower GC doses. The management of PM and DM is similar. Reference: [1] Nuño L, Rheumatol Clin2017; 13:331-337 Disclosure of Interests: Beatriz Joven-Ibáñez Speakers bureau: Celgene, Novartis, MSD, Pfizer, AbbVie, and Janssen, Laura Nuño: None declared, Francisco J López-Longo: None declared, Julia Martinez-Barrio: None declared, Carmen Larena: None declared, Valentina Maldonado : None declared, Carmen Barbadillo: None declared, Paloma García de la Peña: None declared, Irene Llorente : None declared, Eva Tomero Muriel: None declared, Ana Pérez Gómez: None declared, Henry Moruno : None declared, Tatiana Cobo-Ibáñez: None declared, RAQUEL ALMODOVAR: None declared, LETICIA LOJO : None declared, María Jesús García de Yébenes: None declared, Patricia Carreira: None declared